2022
DOI: 10.1001/jamacardio.2022.1988
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Short- and Long-term Outcomes in Patients With Isolated Distal Deep Vein Thrombosis vs Proximal Deep Vein Thrombosis in the RIETE Registry

Abstract: IMPORTANCEInsufficient data exist about the clinical presentation, short-term, and long-term outcomes of patients with isolated distal deep vein thrombosis (IDDVT), that is, thrombosis in infrapopliteal veins without proximal extension or pulmonary embolism (PE).OBJECTIVE To determine the clinical characteristics, short-term, and 1-year outcomes in patients with IDDVT and to compare the outcomes in unadjusted and multivariable adjusted analyses with patients who had proximal DVT. DESIGN, SETTING, AND PARTICIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Commonly, patients with proximal LEDVT had a higher likelihood for development of PE than those with distal LEDVT ( 18 , 23 ). For this, the CHEST guideline emphasizes the importance of thrombus location in treatment choices between serial imaging and anticoagulation therapy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly, patients with proximal LEDVT had a higher likelihood for development of PE than those with distal LEDVT ( 18 , 23 ). For this, the CHEST guideline emphasizes the importance of thrombus location in treatment choices between serial imaging and anticoagulation therapy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by the 2019 European Society of Cardiology (ESC) guideline, thrombus location can also be used to confirm PE ( 38 ). Except for the different anatomic location, proximal and distal LEDVT differ substantially in many aspects, including age, sex, comorbidity burden and VTE risk factors (e.g., recent surgery) ( 18 , 19 , 33 ). After adjusting for confounding factors, we also found that proximal LEDVT was risk factor for developing PE in multivariate analysis and sensitivity analysis (Model 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Pulmonary embolism (PE) is a serious disease of the pulmonary circulation caused by the obstruction of the pulmonary arteries or their branches, which was caused by the dislodgement of emboli mostly from the deep veins of the lower extremities. 2 The incidence of PE in patients with LC is reported to be 6 times higher than that in the population without malignancy. Furthermore, patients with LC are more likely to develop PE than patients with other types of solid tumors, and PE has a mortality risk second only to cancer.…”
Section: Introductionmentioning
confidence: 97%
“…1 Similar to proximal DVT, recurrence risk tends to be higher in patients with cancer-associated or unprovoked IDDVT than in those with transient risk factors. [2][3][4] In high-risk subgroups, long-term recurrence rates may reach those observed in patients with proximal DVT. [2][3][4] Despite this, the management of IDDVT remains uncertain and widely heterogenous across centers worldwide.…”
mentioning
confidence: 99%